IDENTIFIKASI, OEDIPUS-KOMPLEKS DAN KRISIS PARUH BAYA DALAM MIDNIGHT ALL DAY KARYA HANIF KUREISHI: PEMBACAAN PSIKOANALISIS - Muh Arif Rokhman (Sunan Kalijaga State Islamic University Yogyakarta, 2015)
The research is aimed at looking at social relationship and personal problems in the United Kingdom through the eyes of a Pakistani-British writer, Hanif Kureishi. This will be done through the possibility of applying three psychoanalytic concepts, namely identification, Oedipus complex and midlife crisis to literary works. The short stories selected were ‘Strangers when we meet’, ‘That was then’, and ‘Girl’ which were published in Midnight All Day, a short story collection written by Hanif Kureishi, an English writer. The analysis was conducted on the characters of the stories which were subjected to the concepts. The results revealed that the concepts could be applied to the relevant characters. Besides, through the applications, we can see the problems experienced by the characters in the story which may reflect the real people in the United Kingdom.